The anomalous forward premium of EUR/RSD exchange rate - Božović, Miloš; Talijan, Miloš (Industrija, 2015)
Theoretically, exchange rate fluctuations should be positively related to interest-rate differential. This paper empirically examines whether such a relationship holds between EUR/RSD exchange rate and the corresponding interbank interest rates. Estimates on daily data between 2008 and 2015 obtained from a linear regression model indicate that this relationship is in fact negative, consistent with the forward premium anomaly. The result persists over different time horizons. The exchange-rate predictability builds over time. The uncovered interest-rate parity does not hold.
Keywords: Fundamentals; Predictability; Forward premium; Interest Rate; Exchange rate